Cybersecurity for dummies - Steinberg, Joseph (John Wiley & Sons Inc., 2020)
Introducing you to the basics of becoming cyber-secure, this practical book will teach you what threats exist, and how to identify, protect against, detect, and respond to these threats, as well as how to recover if you have been breached. --
Includes index. - Online resource; title from title page (Safari, viewed January 17, 2020)
Keywords: Computer security; Computer networks -- Security measures; Computer Security; Sécurité informatique; Réseaux d'ordinateurs; Sécurité; Mesures; Computer networks; Security measures